2020
DOI: 10.1136/heartjnl-2019-315884
|View full text |Cite
|
Sign up to set email alerts
|

Secondary prevention of cardiovascular disease in China

Abstract: ObjectiveWe aimed to estimate the current use of secondary prevention drugs and identify its associated individual characteristics among those with established cardiovascular diseases (CVDs) in the communities of China.MethodsWe studied 2 613 035 participants aged 35–75 years from 8577 communities in 31 provinces in the China Patient-Centered Evaluative Assessment of Cardiac Events Million Persons Project, a government-funded public health programme conducted from 2014 to 2018. Participants self-reported their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
(31 reference statements)
3
11
1
Order By: Relevance
“…Our results support the finding of previous work that increased disease severity and cardiovascular risk factors were associated with higher prescription rate GDPM [ 12 14 ]. Patients with STEMI or prior MI were more likely to receive GDPM.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results support the finding of previous work that increased disease severity and cardiovascular risk factors were associated with higher prescription rate GDPM [ 12 14 ]. Patients with STEMI or prior MI were more likely to receive GDPM.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of individual drugs, our study reported higher prescription rates of aspirin, clopidogrel, statins and β-blockers than those reported in other studies [ 12 13 14 ]. In contrast, due to the underutilisation of ACEIs/ARBs, the prescription rate of secondary prevention drug combination in our study was relatively low.…”
Section: Discussioncontrasting
confidence: 70%
“…The importance of secondary CVD prevention in adults after a cardiac event is well established yet many patients fail to take appropriate medications. In order to identify individual characteristics associated with use of secondary CVD preventative medications, Lu and colleagues 4 studied the 74 830 participants with known CVD in the China Patient-Centered Evaluative Assessment of Cardiac Events Million Persons Project, out of a total participant group of over 2.6 million people aged 35-75 years of age. The overall use of secondary prevention medications was quite low; 31 .% used antiplatelet drugs, 11% used statins and 8.3% used both medications.…”
Section: Figurementioning
confidence: 99%
“…CVD is a common multifactorial disease [ 17 , 18 ]. CVD including hypertension, pulmonary hypertension, myocardial infarction and stroke is mainly caused by atherosclerosis; obesity and diabetes are major risk factors [ 19 , 20 ]. Studies have demonstrated that ER stress and oxidative stress play roles in the pathogenesis of these cardio-metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%